2020
DOI: 10.1186/s12905-020-00983-x
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer stigma among Indonesian women: a case study of breast cancer patients

Abstract: Background The stigma experienced by cancer patients stems from the association of cancer with death, as cancer is the most feared disease worldwide, especially among cancer patients and their families. The stigma regarding breast cancer screening behaviour has not been critically evaluated and is poorly understood; therefore, we aimed to analyse the stigmatization of breast cancer patients in Indonesia to reduce the morbidity and mortality of breast cancer. Methods A qualitative study using a focus group dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 20 publications
1
34
0
1
Order By: Relevance
“…In Indonesia, a significant number of women are diagnosed for breast cancer in the advanced stage of the disease due to lack of knowledge and awareness, insufficient social support, numerous psychosocial factors, and, often times, the socio-characteristics of breast cancer patients (Setyowibowo et al, 2017;Anwar et al, 2018;Solikhah et al, 2020). A large-scale study in Ghana found that the educational background of a breast cancer patient is significantly associated with breast cancer screening (Agyemang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In Indonesia, a significant number of women are diagnosed for breast cancer in the advanced stage of the disease due to lack of knowledge and awareness, insufficient social support, numerous psychosocial factors, and, often times, the socio-characteristics of breast cancer patients (Setyowibowo et al, 2017;Anwar et al, 2018;Solikhah et al, 2020). A large-scale study in Ghana found that the educational background of a breast cancer patient is significantly associated with breast cancer screening (Agyemang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, further studies have been shown to obtain contradictory results (Rivera-Franco and Leon-Rodriguez, 2018). Meanwhile, higher formal education and socioeconomic status could reduce delayed diagnosis, even though several studies, contrastingly, did not report similar results (Bodapati and Babu, 2013;Lim et al, 2015;Roy et al, 2015;Dyanti and Suariyani, 2016;Solikhah et al, 2020). Residential status and distances to healthcare facilities were also among factors related to delayed diagnosis in breast cancer (Bodapati and Babu, 2013;Thakur et al, 2015).…”
Section: Discussionmentioning
confidence: 98%
“…Most breast cancer patients in Indonesia that come for treatment are usually in the advanced stages, and 63% are in stages III and IV at diagnosis [ 24 , 25 ]. This behavior is related to socio-economic problems, breast cancer stigma, and education levels [ [24] , [25] , [26] ].…”
Section: Discussionmentioning
confidence: 99%
“…From the patient's point of view, Indonesian women do not seek help earlier due to financial problems, rural residence, health expenditure, healthcare access, and lower education level. In addition, other recognized barriers to early detection of breast cancer in Indonesia include belief in traditional medicine and a lack of autonomy in decision making [ [25] , [26] , [27] , [28] ].…”
Section: Discussionmentioning
confidence: 99%